2021
DOI: 10.1177/2325967120969237
|View full text |Cite
|
Sign up to set email alerts
|

Third-Generation Autologous Chondrocyte Implantation at the Knee Joint Using the Igor Scaffold: A Case Series With 2-Year Follow-up

Abstract: Background: For large, locally restricted cartilage defects in young patients, third-generation matrix-supported autologous chondrocyte implantation (ACI) with a variety of scaffolds has shown good mid- to long-term results. Purpose/Hypothesis: This study aimed to monitor the clinical and radiological outcomes of patients who received ACI at the knee joint using the Igor scaffold (IGOR–Institute for Tissue and Organ Reconstruction) at 2-year follow-up. Our hypothesis was that there would be improvements in pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…These results indicate that improvement in pain and knee function is perceived by patients as a real improvement, indicating a satisfactory clinical outcome in these patients. In the case of unilateral lesions, improvement in clinical parameters is accompanied by good integration of the implant in the surrounding cartilage measured by MOCART score, as demonstrated by several authors (19,20). Similar events took place for patients with bilateral lesions studied in the present work: satisfactory clinical outcome was presented together with a high MOCART score, revealing a good integrity of neoformed tissue.…”
Section: Location Of Bilateral Chondral Lesions Of Patients Included In This Work Is Depicted Insupporting
confidence: 86%
“…These results indicate that improvement in pain and knee function is perceived by patients as a real improvement, indicating a satisfactory clinical outcome in these patients. In the case of unilateral lesions, improvement in clinical parameters is accompanied by good integration of the implant in the surrounding cartilage measured by MOCART score, as demonstrated by several authors (19,20). Similar events took place for patients with bilateral lesions studied in the present work: satisfactory clinical outcome was presented together with a high MOCART score, revealing a good integrity of neoformed tissue.…”
Section: Location Of Bilateral Chondral Lesions Of Patients Included In This Work Is Depicted Insupporting
confidence: 86%
“… 17 , 18 Other third-generation ACI studies that included radiological results after 2 years showed the MOCART score was all graded as good. In addition, Zak et al , 19 who used an Igor scaffold, showed that the MOCART 2.0 knee score was 78 at 24 months after implantation. Similar to previous reports, our current study showed that the MOCART 2.0 knee score significantly improved from 57.5 at 6 months after implantation to 71 at 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MOCART 2.0 decreased from 5 to 10 points between 12 and 24 months. 19 Previous studies showed a 3-fold increase in the failure rate of ACI after previous marrow stimulation such as microfracture. 20,21 In addition, the preoperative subchondral bone injury was significantly associated with post-ACI subchondral bone changes.…”
Section: Quantitative Analysismentioning
confidence: 98%
“…Pestka et al and Erdle et al showed that returning to low-intensity and moderate-intensity activities was feasible, but returning to high-intensity or identical-intensity activities to that before surgery was infeasible in 1 year ( 39 , 40 ). Ebert et al and Erggelet et al advised their patients to return to contact and competitive activities 12-month postoperatively ( 41 , 42 ). Furthermore, Niethammer et al compared the rehabilitation process postoperatively.…”
Section: Discussionmentioning
confidence: 99%